Jacques Dupuis and Chalcedon - Yenson, Mark L. (Theological studies, 2019)
This article reexamines Jacques Dupuis's distinction between the action of the Word as such and the action of the Word incarnate. Against recent critics, I argue that Dupuis's Christology is compatible with Chalcedon as interpreted by Leo the Great. I suggest ways in which this Leonine christological approach needs corrective amplification, particularly regarding the unity of Christ and the action of Christ in his risen humanity.